Penguatan Kapasitas Kelembagaan Badan Koordinasi Penataan Ruang Daerah Provinsi Jawa Barat Dalam Pengelolaan Kawasan Lindung Punclut - Leander, Yahya Yoshua; Budiati, Lilin (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
The need for land will increase along with population growth and increase of urbanization into a city. One impact of this phenomenon is the occurrence of functional change conversion in land use and not infrequently shall victimize protected areas. One case of conversion of protected areas into the residential areas, which until now is still a continuing problem, is occurring in the protected areas of Punclut Bandung West Java Province. West Java Province’s BKPRD was formed to address these problems. Therefore, this study is aimed to analyze the level of interest / perception, performance, and capacity of West Java Province’s BKPRD in managing of the Protected Area of Punclut. This study uses quantitative analysis method, Importance Performance Analysis (IPA), to determine the level of interest / perception, performance, and capacity of the West Java Province’s BKPRD in management of Punclut. The descriptive qualitative method is used to analyze the process and mechanism of the West Java Province’s BKPRD activities in making decisions related to the management of Punclut Protected Areas. Of all the analysis steps that have been taken it became known that the gap between the interests level and level of performance on the variable BKRD capacity all show minus values.